Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2015
DOI: 10.1080/0309877x.2014.1000276
|View full text |Cite
|
Sign up to set email alerts
|

A programme-wide training framework to facilitate scientific communication skills development amongst biological sciences Masters students

Abstract: In this article we describe the effectiveness of a programme-wide communication skills training framework incorporated within a one-year biological sciences taught Masters course designed to enhance the competency of students in communicating scientific research principally to a scientific audience. In one class we analysed the numerical marks achieved by students (N 61) for specific communication assignments completed at the start and at the end of the course. This was complemented by questionnaires administe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 25 publications
0
10
0
Order By: Relevance
“…In facilitating the dissemination and uptake of these 'template package' activities, we can look to previous examples of successful pedagogical practice. For example, Divan and Mason (2015) took a programme-wide approach to developing science-specific communication skills in a biosciences graduate program in the UK. One part of this process took the approach of 'writing across the curriculum' (Craig, 2011) which involved integrating communication activities into specialist courses across the degree program with positive results.…”
Section: Discussionmentioning
confidence: 99%
“…In facilitating the dissemination and uptake of these 'template package' activities, we can look to previous examples of successful pedagogical practice. For example, Divan and Mason (2015) took a programme-wide approach to developing science-specific communication skills in a biosciences graduate program in the UK. One part of this process took the approach of 'writing across the curriculum' (Craig, 2011) which involved integrating communication activities into specialist courses across the degree program with positive results.…”
Section: Discussionmentioning
confidence: 99%
“…One Australian study found that explicit teaching of an opinion-editorial writing style in an undergraduate physiology and pharmacology course led to improvements in the students' abilities to communicate effectively in writing with the lay public (Moni, Hryciw, Poronnik, & Moni, 2007). Another study based in the UK found that making expectations explicit when teaching communication in a science graduate program was important for quality learning (Divan & Mason, 2015). This indicates that there has been some documented success in applying the lens of explicit instruction to teaching communication skills in undergraduate science.…”
Section: Evidence-based Curriculum Developmentmentioning
confidence: 97%
“…It was discovered that 27 articles discussed AQF compliant courses. The articles identified relating to AQF compliant courses in the university sector covered a wide diversity of disciplines and subject areas including: accounting [7]; business coaching [8]; economics [9]; event management [10]; health degrees [11]; law [12]; sciences [13]; broad tertiary focus [14]; employment outcomes or precise skills [15]; Vocational Education and Training (VET) courses [16]; and undergraduate courses [17]. Others simply conversed about their programs or skills but were not connected to the AQF and were omitted.…”
Section: Overviewmentioning
confidence: 99%